2017
DOI: 10.1007/s11356-017-9826-3
|View full text |Cite
|
Sign up to set email alerts
|

Mushrooms: from nutrition to mycoremediation

Abstract: Mushrooms are well known as important food items. The uses of mushrooms in the cuisine are manifolds and are being utilized for thousands of years in both Oriental and Occidental cultures. Medicinal properties of mushrooms show an immense potential as drugs for the treatment of various diseases as they are rich in a great variety of phytochemicals. In this review, we attempted to encompass the recent knowledge and scientific advancement about mushrooms and their utilization as food or curative properties, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 136 publications
0
25
0
1
Order By: Relevance
“…White button mushroom Agaricus bisporus [MB#292246] is a popular foodstuff worldwide. This mushroom and other species collected from the wild or cultivated are considered as a good source of proteins, vitamins and mineral constituents (potassium, phosphorus, zinc and copper or selenium) but also of antioxidants and with antibacterial, anti-inflammatory, antitumor, and immunomodulatory properties -see reviews by several authors [4,14,32,33,37].…”
Section: Introductionmentioning
confidence: 99%
“…White button mushroom Agaricus bisporus [MB#292246] is a popular foodstuff worldwide. This mushroom and other species collected from the wild or cultivated are considered as a good source of proteins, vitamins and mineral constituents (potassium, phosphorus, zinc and copper or selenium) but also of antioxidants and with antibacterial, anti-inflammatory, antitumor, and immunomodulatory properties -see reviews by several authors [4,14,32,33,37].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, mycoremediation is another important biotechnological application of fungi. Here, mainly mushroom-forming fungi are used to degrade or sequester toxic pollutants including metals from the environment (Chatterjee et al 2017;Kapahi and Sachdeva 2017).…”
Section: Application Potentials Of Fungal Biotechnology: a Brief Surveymentioning
confidence: 99%
“…However, research on the health effects of mushrooms has only emerged and been developed in recent decades. To date, an increasing number of in vivo and in vitro studies have suggested the beneficial effects of mushrooms on health, such as antioxidation, anti‐inflammation, immunomodulation, etc …”
Section: Introductionmentioning
confidence: 99%
“…To date, an increasing number of in vivo and in vitro studies have suggested the beneficial effects of mushrooms on health, such as antioxidation, anti-inflammation, immunomodulation, etc. 3 Additionally, mushrooms also reportedly have anticancer properties and effects against tumor development. 4 In vivo and in vitro evidence has shown that mushrooms have the potential to prevent several kinds of cancers (e.g., those of the breast, bladder, colon and lung), including prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation